2012
DOI: 10.1080/10495398.2011.652325
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Splicing of Testis-Specific Lactate Dehydrogenase C Gene in Mammals and Pigeon

Abstract: The objective of the present study was to confirm the widespread existence of alternative splicing of lactate dehydrogenase c (ldhc) gene in mammals. RT-PCR was employed to amplify cDNAs of ldhc from testes of mammals including pig, dog, rabbit, cat, rat, and mouse, as well as pigeon. Two to six kinds of splice variants of ldhc were observed in the seven species as a result of deletion of one or more exons or insertion of partial sequence of an intron in the mature mRNA. The deleted exons occur mostly in exons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The available data describing splicing events within the reproductive system of the birds focused on 2 genes: chicken DMRT1 and pigeon LDHC ( Zhao et al, 2007 ; Huang et al, 2012 ). The presence of 3 splicing events situated within the DMRT1 locus was also detected in our study; however, no significant expression changes between particular parts of the reproductive tract were recorded.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The available data describing splicing events within the reproductive system of the birds focused on 2 genes: chicken DMRT1 and pigeon LDHC ( Zhao et al, 2007 ; Huang et al, 2012 ). The presence of 3 splicing events situated within the DMRT1 locus was also detected in our study; however, no significant expression changes between particular parts of the reproductive tract were recorded.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies on AS have been reported in relation to bird reproduction ( Zhao et al, 2007 ; Huang et al, 2012 ; Lang et al, 2020 ; Rogers et al, 2021 , Sun et al, 2021 ). AS of testis-specific lactate dehydrogenase C ( LDHC ) and doublesex- and mab-3-related transcription factor 1 ( DMRT1 ) were reported for chicken and pigeon ( Zhao et al, 2007 ; Huang et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4F). The lactate dehydrogenase (LDH), mainly consisting of LDHA and/or LDHB subunits, catalyzes the final step of lactate synthesis, namely conversion of pyruvate to lactate (Huang et al 2012). Concerning the testicular function of LDHA, two aspects should be emphasized.…”
Section: Figurementioning
confidence: 99%